Verifikasi Metode ELISA (Enzym Linked Immunosorbent Assay) Untuk Penentuan Kadar AMH (Anti Mullerian Hormone) - Irvan Ipandi; Ashon Sa'adi; Sudjarwo Sudjarwo (Jurnal Surya Medika (JSM), 2019)
Validation is the process of confirming that the method used has capabilities that are consistent with what is needed while being used continuously. The AMH ELISA kit has carried out a method validation process before marketed and used in a laboratory to determine AMH levels. AMH is a specific biomarker used to diagnose PCOS patients. The laboratory can adopt a validated procedure but the laboratory still needs to confirm its ability to apply this method. Verification is the provision of objective evidence that the measured parameters meet the specified requirements. The purpose of this study was to find out how well verification of the ELISA AMH kit and comparing the calculation of 4 PL with linear regression. Based on the statistical test obtained p = 0.871 (p>0.05). It can be said that there was no significant difference between Optical Density days 1 and 7(p = 0.05). Linear regression equation (r) 0.9543 (p = 0.000; p <0.05) while in equation 4 PL (r) 1,000. The ELISA kit AMH method meets the verification requirements. The 4PL model calibration curve is more suitable to be used in the AMH ELISA kit than the linear regression model.